Adjustable PAPR reduction for DFT‐s‐OFDM via improved general precoding scheme. Issue 14 (1st July 2018) - Cho, L.; Liao, H.‐C.; Hsu, C.‐Y.
Abstract : An improved and specification‐compatible general precoding scheme (GPC) for adjustable peak‐to‐average power ratio (PAPR) reduction in discrete Fourier transform spread orthogonal frequency division multiplexing (DFT‐s‐OFDM) is proposed. Through the rearrangement of periodic padding for precoded data symbols in the GPC precoding matrix, the proposed algorithm does not increase any computational complexity compared to the original GPC. The LTE‐based simulation shows the proposed algorithm has a better improvement of PAPR reduction especially in low‐order modulations and the performances can be scaled to the other transmission bandwidth. These works contribute to the flexibility of DFT‐s‐OFDM for supporting 5G transmission over miscellaneous power amplifiers.